PERANCANGAN APLIKASI SISTEM INFORMASI BIMBINGAN KONSELING PADA SEKOLAH MENENGAH KEJURUAN - Purwa Hasan Putra; Muhammad Syahputra Novelan (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2020)
In this case the making of information systems guidance counseling is very necessary. Where this counseling guidance information system not only records the number of violations, but also the complete identity of students, achievements and special problems of students. So with this guidance counseling information system the teacher can monitor and assist students in the study period at the school. The results of the research system are expected to be able to facilitate students to convey their problems and get guidance from guardian or counseling teachers wherever and whenever. Guidance counseling system can provide information in the form of children's behavior, children's achievements, and others. Counseling guidance system can make it easier for teachers and parents to monitor student behavior, each process will be recorded and stored in a database so that it is expected that data is safer and will be easier to process into useful information